2011
DOI: 10.1016/j.bone.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loads and cortical bone geometry in healthy children and young adults

Abstract: Muscle and bone form a functional unit. While muscle size is a useful surrogate of mechanical load on bone, the independent contributions to bone strength of muscle force, muscle size, gravitational load (body weight), and physical activity have not been assessed. 321 healthy participants (32% black, 47% male), age 5 to 35 years were assessed. Peak dorsiflexion muscle torque (ft-lbs) of the ankle was assessed using isometric dynamometry. Tibia peripheral quantitative computed tomography measures included polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 29 publications
5
59
1
Order By: Relevance
“…We recently reported that total physical activity was positively associated with section modulus independent of age, sex, race, Tanner stage, tibia length, and muscle area. 21 …”
Section: Physical Activity Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that total physical activity was positively associated with section modulus independent of age, sex, race, Tanner stage, tibia length, and muscle area. 21 …”
Section: Physical Activity Questionnairementioning
confidence: 99%
“…45 Peak isometric torque (foot-pounds) was measured in triplicate at 20°dorsiflexion, and the highest value was recorded, as previously described in the reference participants. 21 This measurement was used because the tibialis anterior attaches directly to the tibia (the bone of interest in this study) and causes dorsiflexion of the ankle. The coefficient of variation in our laboratory was 4.3%.…”
Section: Biodex Measurement Of Muscle Torquementioning
confidence: 99%
See 1 more Smart Citation
“…This theory posits that bone adapts to the mechanical loads that are placed upon it during muscle contraction. Total body lean mass and muscle cross-sectional area (MCSA) are common surrogates of the muscular contractile forces of which bone is particularly responsive as muscle size and strength are closely related [6]. As a second example, pathogenic fat depots, for example, adiposity stored within the skeletal muscle, have piqued recent interest, as muscle fat in adults has been shown to be predictive of suboptimal bone outcomes and hip fracture [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Among many factors affecting bone mass, body weight is a strong and positive predictor acting through mechanical stress, which in turn increases osteogenesis and bone mineral density (BMD) [1]. In turn, it has been suggested that the reduction in body weight brings about bone loss [2].…”
Section: Introductionmentioning
confidence: 99%